Selection of site specific Eucalyptus camaldulensis and Eucalyptus tereticornis clones for Ariyalur region (Tamil Nadu) based on its higher Productivity - Vijayaraghavan, A.; Sivakumar, V. (IJRDO-Journal of Applied Science, 2017)
Eucalyptus camaldulensis clones were shortlisted based on individual tree superiority observed in the multi-location clonal trials for growth attributes like height, girth at breast height and volume through Index selection method. These clones were planted along with commercially planted clones in southern peninsular India , seedlings raised from improved seed orchard source and genetically poor seedlings procured locally during the year 2009. The above clones and seedlings were planted near Nachiarpettai located near Ariyalur (Tamil Nadu) to identify the best performing site specific clones in Tamil Nadu. It falls in the range of 11° 07’45.91’’N latitude to 79°13’15.94’’E longitude. The growth parameters like height, girth at breast height and its volume were recorded up to 3 years. The results confirm that the clones are best selected and tested in environments similar to those where they will be deployed. Ranking of the 33 commonly planted clones and two seed lots showed that Clone C31, C9, C196 and C17 were consistently superior in their growth performance when compared to all other clones, seed lots and some of the commercially cultivated clones with respect to height, girth and volume although the sequence changed for each characters. Based on the study it was concluded that the clones viz., Clone C31, C9, C17 and C196 are best suitable for the area in and around Nachiarpettai (Ariyalur) having the same soil property (Sandy loam) and climatic conditions.